Empowering coastal women in improving family economy in Margasari - Utomo, Agus Budi; Rochana, Erna; Widiastuti, Endang Linirin; Hartoyo, Hartoyo; Riantini, Maya (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2025)
This study aims to see the empowerment efforts of coastal women in improving the family economy in Margasari Village, Labuhan Maringgai District, East Lampung Regency. This study used a qualitative research type with an ethnographic approach. The focus of the study was on four Poklahsar in Margasari Village. Data collection techniques were carried out through observation, interviews, and documentation studies. Then, qualitative data analysis was carried out with the stages of data reduction, data presentation, and data collection. The results of the study are that the empowerment of coastal women in Margasari Village through Poklahsar is carried out by providing various training, workshops, mentoring and assistance, both capital and production support facilities. Although the empowerment carried out has been quite massive, the impact of increasing income for families is still not significant because the marketing of processed food products produced by Poklahsar has not been optimal.